Genetic Enhancement Of Leaf Rust Resistance In Bread Wheat (Triticum Aestivum L.) Through Marker-Assisted Introgression Of Lr24 And Lr28 (Applied Biological Research, 2019)
The present study was initiated with the objective of marker-assisted  introgression of Lr24 and Lr28, wheat leaf rust resistance genes, into an elite  susceptible bread wheat genotype MP3299 from NIL-PBW 343. Marker assisted selection alongwith screening of genotypes under epiphytotic conditions was undertaken in this study. SCAR molecular markers SCS73719 and SCS421570 linked to Lr24 and Lr28, respectively, confirmed in  segregating population of MP3299 x NIL-PBW 343, were further evaluated  for leaf rust resistance under artificial leaf rust condition. In F4 and F5  populations, high degree of leaf rust resistance was observed in plants  carrying both Lr24 and Lr28 genes as compared to the plants with individual  leaf rust resistance gene Lr24, followed by Lr28. Significant correlation and  regression were observed between most of the agronomic traits and coefficient of incidence. Six Lr28 homozygous plants identified with high  degree of leaf rust resistance were advanced for yield trials. The identified  lines seem potential resistance sources and superior recombinants for future  breeding programmes.
Keywords: Coefficient of incidence; marker-assisted introgression; rust resistance; SCAR marker